Sets of singular points of actions of finite groups by (S^n)^k - Plakhta , L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Realizations of integral D_3-modules of rank 2 on (S^n)^k for the dihedral groups D_3 are studied. Cohomologies of the sets of the singular points of the actions of the semidirect products Z / p ightthreetimes Z / q and the quaternion groups Q on (S^n)^k are investigated.